Communication Dimensions of Healthcare Engagement and Patient Health Literacy for Immigrant Populations: A Comprehensive Review - Qassem Mahdi Busrour (International Journal of Scientific Research and Innovative Studies, 2024)
Immigrant populations face unique challenges in accessing healthcare, often stemming from cultural, linguistic, and systemic barriers. Effective communication is essential for improving healthcare engagement and patient health literacy among immigrants. This review examines the communication dimensions that influence healthcare experiences, the impact of health literacy on outcomes, and strategies to bridge gaps in care for immigrant populations. The review highlights the importance of culturally and linguistically appropriate services, community-based interventions, and health systems reforms to foster equitable healthcare access. Received Date: July 08, 2024 Accepted Date: July 29, 2024 Published Date: August 01, 2024 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/291 DOI: https://doi.org/10.5281/zenodo.14549625